Impact of COVID-19 on outpatient dental production (Research, Society and Development, 2022)
Introduction: Since the implementation of the National Oral Health Policy, an increase in oral health teams and a greater variety of dental procedures performed have been observed. However, the new epidemiological scenario imposed by COVID-19 affected outpatient dental production, compromising the advances made. Objective: To assess the impact of COVID-19 on outpatient dental production. Methods: This is an interrupted time series carried out with secondary data from the Unified Health System, in the period between 2016 and 2021, dividing it into two time segments, one before and one after the first case diagnosed in Brazil. The R Studio software was used with a segmented linear regression model. Autocorrelation was corrected using Prais-Winsten regression. Results: There was a statistically significant change in the number of procedures after the interruption (p